Thermoset Polymer Splicing Study Using a variation of welding - Adi Prastyo Utomo; Prantasi Harmi Tjahjanti (Universitas Muhammadiyah Sidoarjo, 2021)
There is not much plastic welding currently done and not much research has been done on plastic welding. The purpose of this study was to study the use of welding variations used to join the thermoset polymer material. The thermoset polymer materials used are acrylic, melamine and bakelit with the test sample measuring 80mm in length, 30mm in width and 3mm in thickness. Variations in welding are used using hot gas welding, electric soldering and gas torches. The test method is carried out after welding to determine the porosity of the weld using a penetrant liquid. Hardness testing was also carried out. The best welding results are shown on acrylic material using electric solder, showing that the amount of porosity is the least, and has the highest hardness test.